PERAN SILPA SEBAGAI PEMODERASI DALAM MENENTUKAN FAKTOR YANG MEMPENGARUHI ALOKASI BELANJA MODAL - Jaeni, Jaeni -; Kartika, Andi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
This study aims to examine the effect of Regional Original Income (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) on Capital Expenditures which are moderated by Remaining Over Budget Financing (SiLPA). The population in this study is the Regency / City of Central Java Province which consists of 35 Regencies / Cities. This study uses secondary data in the form of the 2015 - 2017 APBD Realization Report. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially Regional Original Income (PAD), General Allocation Fund (DAU), and DAK affect the Capital Expenditures. But the Remaining More Budget Financing (SiLPA) partially does not affect Capital Expenditures. While the Remaining More Budget Financing (SiLPA) partially does moderate the relationship of Allocation Funds (DAK) to Capital Expenditures and Regional Original Revenue (PAD), General Allocation Fund (DAU) does not moderate the relationship to Capital Expenditures.